1995
DOI: 10.1093/bja/75.5.616
|View full text |Cite
|
Sign up to set email alerts
|

Effects of graded infusion rates of propofol on cardiovascular haemodynamics, coronary circulation and myocardial metabolism in dogs

Abstract: We have studied the effects of a 30-min infusion of propofol 6, 9, 12, 15, 18 and 21 mg kg-1 h-1 on cardiovascular haemodynamics, coronary circulation and myocardial metabolism in 12 mongrel dogs. Mean plasma concentrations of propofol after infusion of 6 and 21 mg kg-1 h-1 increased from 2.9 (SEM 0.3) to 11.5 (0.1) micrograms ml-1. Propofol produced a progressive decrease in arterial pressure. Heart rate tended to decrease at 15, 18 and 21 mg kg-1 h-1 and cardiac index decreased significantly at infusion rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…According to NAKAIGAWA et al (1995), the CI decrease is related to the change in SVI during propofol anesthesia and it is believed that the same situation happened on our study (Figure 1). Changes in SVI depend on several factors, such as changes in preload and in myocardial contractility.…”
Section: Resultssupporting
confidence: 79%
“…According to NAKAIGAWA et al (1995), the CI decrease is related to the change in SVI during propofol anesthesia and it is believed that the same situation happened on our study (Figure 1). Changes in SVI depend on several factors, such as changes in preload and in myocardial contractility.…”
Section: Resultssupporting
confidence: 79%
“…It is reported that SV and CO decreased during propofol anesthesia in human [13], pig [9] and dog [18] similar to other anesthetics. However, there is another report in human where propofol did not influence SV or CO probably because some depressive effects of propofol on cardiovascular system was masked by the effects of increased PaCO 2 caused by moderate respiratory impairment [8].…”
Section: Discussionmentioning
confidence: 53%
“…In vivo, propofol produces a decrease in myocardial blood flow and Mvo 2 (1,2). Although numerous in vitro studies reported a coronary vasodilation, previous results remain a subject of controversy.…”
Section: Discussionmentioning
confidence: 99%
“…T he attractive pharmacokinetic properties of propofol and the use of new anesthetic techniques, such as the target-controlled infusion technique, explain the increased use of propofol. In vivo, propofol induces a decrease in myocardial blood flow and myocardial oxygen consumption (1,2). Although in vitro studies reported significant coronary effects of propofol, these results are variable (3)(4)(5)(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%